Relationship between auditors’ fees and earnings management - Lopo Martinez, Antonio (2017)
This study investigates the relationship between audit fees and earnings management in theBrazilian market. In response to the research question, we used a sample of 300 firms listed onthe BM&FBovespa for which it was possible to identify the amount paid to the auditors, using data gathered from the Economatica® database and the website of the Brazilian Securities Commission (Comissão Brasileira de Valores Mobiliários [CVM]). We analyzed the regressions with the aim of supporting or refuting the hypothesis that audit firms that charge less for their service tend to be more relaxed regarding earnings management by their client companies. The results support this hypothesis. The main contribution of this study is the possibility of stating that more aggressive earnings management occurs predominantly among firms that pay less than expected for audit services. This study evidences the perception of risk by audit firms and how this is reflected in the audit fees charged.